A Novel Mass-Energy Equivalence from Lorentz Factor and Relativistic Momentum - Chinnaraji Annamalai (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Initial interpretations of Einstein’s mass-energy equivalence often foster the misconception that an object’s mass increases as its velocity approaches the speed of light. This article aims to correct this outdated view by presenting a modern perspective where mass is treated as an invariant property. By redefining momentum through proper time and time dilation, this paper provides a rigorous derivation of relativistic momentum and the accurate mass-energy equation while bridging these concepts to the fundamental energy-momentum relation.